The Principle of Good Faith In The Filing of A Bankruptcy Application by A Separated Creditor Against A Debtor (Case Study Of Supreme Court Decision Number 1434 K/Pdt.Sus-Pailit/2020) - Ariansyah Kurniawan; Iwan Erar Joesoef; Atik Winanti (Dinasti Research, 2026)
This study aims to analyze the application of the principle of good faith in the submission of bankruptcy petitions by secured creditors against debtors, as set forth in Supreme Court Decision Number 1434 K/Pdt.Sus-Pailit/2020 and assess the judge's considerations in distinguishing the use of legitimate rights from abuse of authority by comparing it with Supreme Court Decisions Number 704 K/Pdt.Sus-Pailit/2018 and Number 1230 K/Pdt.Sus-Pailit/2019. This study employs a juridical normative method under case and statutory approaches. The legal materials consist of primary, secondary, and tertiary legal materials, which are analyzed qualitatively through the interpretation of legal principles, doctrines, and the ratio decidendi of the decision. The results indicate that the Supreme Court considers the bankruptcy petition by secured creditors in Decision Number 1434 K/Pdt.Sus-Pailit/2020 does not violate the principle of good faith because it is submitted to protect the legal interests of collateral whose economic value is threatened. Conversely, in Decisions No. 704 K/Pdt.Sus-Pailit/2018 and No. 1230 K/Pdt.Sus-Pailit/2019, the bankruptcy petition was rejected because it was deemed disproportionate and potentially pressured the debtor. The study formulates an ideal model for a bankruptcy petition by secured creditors that emphasizes collateral protection, does not involve abuse of rights, and is preceded by alternative resolution efforts. This model reflects the principles of balance, appropriateness, and the objective of bankruptcy law to protect the interests of both creditors and debtors fairly and proportionally in the current bankruptcy court practice in Indonesia, and contributes to development.